2013
DOI: 10.1128/mbio.00388-13
|View full text |Cite
|
Sign up to set email alerts
|

Within-Host Evolution of Burkholderia pseudomallei over a Twelve-Year Chronic Carriage Infection

Abstract: Burkholderia pseudomallei causes the potentially fatal disease melioidosis. It is generally accepted that B. pseudomallei is a noncommensal bacterium and that any culture-positive clinical specimen denotes disease requiring treatment. Over a 23-year study of melioidosis cases in Darwin, Australia, just one patient from 707 survivors has developed persistent asymptomatic B. pseudomallei carriage. To better understand the mechanisms behind this unique scenario, we performed whole-genome analysis of two strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(141 citation statements)
references
References 71 publications
3
138
0
Order By: Relevance
“…MSHR6137 was also subjected to WGS using the 454 GS FLX ϩ platform (454 Life Sciences, Branford, CT, USA). Genome assembly for this strain was performed as previously described (12). The final genome contains 65 contigs totaling 7,208,016 bp, with an N50 of 258,651 bp, and encodes a predicted 6,656 proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSHR6137 was also subjected to WGS using the 454 GS FLX ϩ platform (454 Life Sciences, Branford, CT, USA). Genome assembly for this strain was performed as previously described (12). The final genome contains 65 contigs totaling 7,208,016 bp, with an N50 of 258,651 bp, and encodes a predicted 6,656 proteins.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain greater resolution, we performed whole-genome sequencing (WGS) on B. pseudomallei obtained from these two cases, from their water supply, and from other melioidosis patients and environmental samples from the surrounding region. PCR-based multilocus variable-number tandem repeat (VNTR) analysis (MLVA) of four loci (10) was incorporated to augment WGS short read data, which are unable to span paralogous or certain highly repetitive loci in B. pseudomallei (11,12). As a novel aspect of this study, we performed genomewide phylogenetic analysis of small insertions/deletions (indels), which largely comprise short read-mappable VNTRs across the B. pseudomallei genome, to increase our resolution among closely related isolates.…”
mentioning
confidence: 99%
“…Previous studies on long-term bacterial adaptation have reported genome reduction by deletion of genes encoding nonessential functions, particularly for environmental-opportunistic pathogens (Rau et al 2012;Price et al 2013;Sharma et al 2014). Longterm mutation accumulation studies showed that B. cenocepacia has low genome-wide mutation rates, with many of the mutations biased toward deletions (Dillon et al 2015).…”
Section: Recurrent Genomic Changes In B Cenocepacia During Long-termmentioning
confidence: 99%
“…These relatively large chromosomes encode several putative virulence factors, including quorum sensing, type III secretion systems, and the capsular polysaccharide (13). The chromosomes are thought to be highly dynamic, evidenced by the presence of several recently acquired mobile genetic elements in the chromosome (6,12) and the extensive genetic diversification observed over time in a single patient (14,15). The portion of the genome with high variability between strains may contribute to virulence and antibiotic resistance (16).…”
Section: Microbiologymentioning
confidence: 99%